Validity and diagnostics of the Reading the Mind in the Eyes Test (RMET) in non-demented amyotrophic lateral sclerosis (ALS) patients - Aiello, Edoardo Nicolò; Carelli, Laura; Solca, Federica; Torre, Silvia; Ferrucci, Roberta; Priori, Alberto; Verde, Federico; Silani, Vincenzo; Ticozzi, Nicola; Poletti, Barbara (Frontiers in Psychology, 2022)
Background. The present study aimed at exploring the construct validity and diagnostic properties of the Reading the Mind in the Eyes Test (RMET) in non-demented amyotrophic lateral sclerosis (ALS) patients. Materials. N=61 consecutive patients and N=50 healthy controls (HCs) were administered the 36-item RMET. Additionally, patients underwent a comprehensive assessment of social cognition via the Story-Based Empathy Task (SET), which encompasses three subtests targeting Causal Inference, Emotion Attribution (SET-EA) and Intention Attribution (SET-IA), as well as global cognitive (Edinburgh Cognitive and Behavioural ALS Screen) and behavioural screening (Frontal Behavioural Inventory; Dimensional Apathy Scale; Beck Depression Inventory; State- and Trait-Anxiety Inventory-Y). Construct validity of the RMET was tested by regressing it within a stepwise model that encompassed as predictors the abovementioned cognitive and behavioural measures, covarying for demographic and motor confounders. Receiver-operating characteristics analyses allowed to explore intrinsic and post-test properties of the RMET both in discriminating patients from HCs and in identifying patients with a defective SET-EA performance. Results. The RMET was solely predicted by the SET-EA (p=.003) and SET-IA (p=.005). RMET scores showed high accuracy both in discriminating patients from HCs (AUC=.81), and in identifying patients with a defective SET-EA score (AUC=.82), with adequate-to-optimal both intrinsic and post-test properties. Discussion. The RMET is a convergently and divergently valid measure of affective social cognition in non-demented ALS patients, also featured by optimal intrinsic and post-test diagnostic properties in both case-control and case-findings scenarios.